A Phenomenological Study on Lombok Island’s Competitiveness as Tourist Destination through Tourism Actors’ Perception - Sakti, Dwi Putra Buana; Armanu, Armanu; Rofiaty, Rofiaty; Rohman, Fatchur (Interdisciplinary Social Studies, 2023)
Background: The competitiveness of Lombok Island as a tourist destination is an interesting research topic because there has been no research that examines it. Until now, knowledge about the factors that determine the competitiveness of Lombok Island as a tourist destination has not been widely disclosed to public spaces. On the other hand, the phenomenon of the competitiveness of Lombok Island as a tourist destination is believed to be able to complement the existing model of competitiveness of tourist destinations by adding elements that are local-special-narrow. Aim: This study aims to analyze the competitiveness of Lombok Island as a tourist destination for domestic tourists based on the perspective of tourism actors. Method: Research on the competitiveness of tourist destinations in Lombok Island was carried out using a qualitative phenomenological approach. The research is aimed at obtaining meanings related to the determining factors of the competitiveness of Lombok Island as a tourist destination according to the perception of tourism actors on the island of Lombok. Findings: The result of this study is the acquisition of attributes related to the determining factors for the competitiveness of Lombok Island as a tourist destination. The competitiveness of Lombok Island as a tourist destination is determined by four attributes, namely (1) natural attributes, (2) attributes that can be created, (3) supporting attributes, and (4) reinforcing attributes. The four attributes obtained in this study form a framework for the competitiveness of Lombok Island tourist destinations which are specific only to the island of Lombok.